Investigating factors that influence the practice of exclusive breastfeeding among mothers in an urban general hospital in Ghana: a cross-sectional study - Baaba Dadzie; Fidelis Bayor; Abdul-Razak Doat; Jamilatu B. Kappiah; Collins Adombire Akayuure; Aubrey A. Lamptey; Vida Nyagre Yakong; Sylvanus Kampo (BMC, 2023)
Abstract Background In Ghana, only 52% of mothers exclusively breastfeed their babies and the rate of increase has been steadily slow across all geographical areas of Ghana. The purpose of this study was to determine the various factors that influence exclusive breastfeeding (EBF) among mothers who visited the child welfare clinic at the Tema General Hospital, Accra, Ghana. Methodology This descriptive cross-sectional study was carried out at the Child Welfare Clinic of the Tema General Hospital, Accra, Ghana. A random sampling technique was used to recruit mothers with children between the ages of 6 months and 24 months attending the Child Welfare Clinic. Mothers were interviewed with the aid of a structured questionnaire. Results Out of the 222 of mothers interviewed, 68.8% of them exclusively breastfed their infants up to 6 months. Mothers who have good knowledge were more than 3 times (AOR = 3.484, 95% CI 1.200, 10.122, P = 0.022) likely to breastfeed their children exclusively. Those who had positive attitudes towards EBF were about 4 times (COR: 4.018, 95% = 1.444, 11.181, P = 0.008) more likely to exclusively breastfeed than those who had poor attitudes towards EBF. Also, mothers whose spouses complained about EBF were about 3 times (AOR: 2.655, 95% CI 0.620, 11.365, P = 0.018) at increased odds of not exclusively breastfeeding their babies. Conclusions High rate of EBF among mothers who visited the child welfare clinic was found. The mothers' level of knowledge and attitude towards EBF significantly influenced the 6 months of EBF. Spouses also showed a high influence on whether or not mothers should exclusively breastfeed their babies.